From computation to communication: unveiling Salmonella metabolic plasticity and public perceptions of the microbial world using multi-omics and thematic analysis - Kokkinias, Katherine, author; Wrighton, Kelly C., advisor; Kelp, Nicole, committee member; Borlee, Brad, committee member; Weir, Tiffany, committee member (Colorado State University. Libraries, 2024)
Research and communication on microorganisms and microbiomes has become increasingly important in recent decades due to evolving threats posed by infectious diseases and microbial contributions to ecological systems. Antibiotic resistance presents a significant challenge to global health equity, with nontyphoidal Salmonella infections being a prominent concern. Despite its prevalence and impact, Salmonella infections lack effective vaccines, posing a serious threat to vulnerable populations. Concurrently, misconceptions and misinformation about microorganisms and microbiomes can arise given the dynamic nature of scientific research which can hinder effective science communication and health outcomes. Despite this, little is known about public perceptions of microorganisms and microbiomes, impeding our ability to create effective, tailored science messaging. Both basic pathogen research and science communication research are essential to identify targeted prevention strategies and to understand public perceptions of microorganism and microbiomes. This dissertation spans microbiome and science communication research, employing both qualitative and quantitative methods. The overarching research goals of this dissertation are to 1) lay the groundwork for therapeutics by studying Salmonella metabolism and metabolic plasticity, 2) develop a multi-omics repository to expand the usability of our omics datasets, and 3) understand public perceptions of microorganisms and microbiomes to improve future microbial science communication efforts. Chapter 1 as the introductory chapter reviews the current state of Salmonella and science communication research, providing a context for the new research presented in this dissertation. Through a multi-omics approach, Chapter 2 explores the metabolic strategies of Salmonella under different diet backgrounds and over time, offering insights into potential therapeutic targets. Chapter 3 introduces the CBA_DREAMM database, facilitating centralized storage and sharing of multi-omics datasets to enhance communication of our research and collaboration in microbiome research. Chapter 4 investigates public perceptions of microbes and microbiomes in the United States, revealing a need for tailored science communication efforts. Additionally, the study emphasizes the importance of clear communication, trust, and emotions, like apathy, in science communication. Chapter 5 is the conclusion, summarizing findings from Chapter 2, 3, and 4 and describing future directions. By bridging natural and social sciences, this dissertation aims to inform strategies for tackling global issues by advancing microbiome and science communication research.
Zip file contains four data spreadsheets.
Keywords: data repository; RNA-seq; science communication; multi-omics; CBA mouse model; Salmonella